Impact of active constructive leadership and passive corrective leadership on collective organizational commitment. Issue 7 (5th September 2016) - Wei, Feng; Lee, Jean; Kwan, Ho Kwong
Abstract : Purpose: The purpose of this paper is to test the factor structure of the multifactor leadership questionnaire (MLQ) in the Chinese context and determine whether leader-member exchange (LMX) mediates the effects of active constructive leadership (ACL) and passive corrective leadership (PCL) on subordinates' organizational commitment at the group level. Design/methodology/approach: Questionnaires were completed by two employee samples. The first sample consisted of 615 employees from five pharmaceutical companies. The second sample consisted of 676 employees from 144 teams. Exploratory factor analysis, confirmatory factor analysis and structural equation modeling were used to test the hypotheses. Findings: The factor analysis results showed two types of leadership in the data: ACL and PCL. The structural equation modeling showed that LMX mediated the effect of leadership on collective organizational commitment. Research limitations/implications: The data were cross-sectional in nature. Furthermore, leadership and LMX were both measured from the perspective of followers. Practical implications: Managers must realize that leadership is an art that requires not only the self-cultivation of individual behavior, but also appropriate and intelligent conduct when interacting with followers. Team leaders also must pay attention to both their high quality relationships with subordinates and the mutual influence within their groups. Originality/value: The current study makes an empirical contribution to the psychometric properties of the MLQ, suggesting a higher two-factor structure appropriate for Chinese employees. It also clarifies the relationships between leadership, LMX and organizational commitment at multiple levels.